Regulation and Function of Interferon-Lambda (IFNλ) and Its Receptor in Asthma - Krammer, Susanne; Sicorschi Gutu, Cristina; Grund, Janina C.; Chiriac, Mircea T.; Zirlik, Sabine; Finotto, Susetta (Frontiers in Immunology, 2021)
Asthma is a chronic respiratory disease affecting people of all ages, especially children, worldwide. It often begins during infancy with heterogeneous clinical presentation, severity and pathophysiology. Exacerbations of asthma disease can be triggered by many factors, including viral respiratory tract infections. Rhinovirus (RV) induced respiratory infections are the predominant cause of the common cold and also play a crucial role in asthma development and exacerbations. Rhinovirus mainly replicates in epithelial cells lining the upper and lower respiratory tract. Type III interferons also known as IFN-lambda are potent immune mediators of resolution in infectious diseases but they are known to be involved in autoimmune diseases as well. The protective role of type III IFNs in antiviral, antibacterial, antifungal and antiprotozoal functions is of major importance for our innate immune system. The IFN-lambda receptor is expressed in selected types of cells like epithelial cells, thus orchestrating a specific immune response at the site of viruses and bacteria entry into the body. In asthma, IFN-lambda seems to restrict the development of Th2 cells, which are induced in the airways of asthmatic patients. Several studies described type III IFNs as the predominant type of interferon increased after infection caused by respiratory viruses. It efficiently reduces viral replication, viral spread into the lungs and viral transmission from infected to naive individuals. Several reports showed that bronchial epithelial cells from asthmatic subjects have a deficient response of type III interferon after RV infection ex vivo. Toll like Receptors (TLRs) recognize pathogen-associated molecular patterns (PAMPs) expressed on infectious agents, and induce the development of anti-viral and anti-bacterial immunity. We recently discovered that activation of TLR7/8 resulted in enhanced IFNλ receptor (IFNλR) mRNA expression in PBMCs of healthy and asthmatic children, opening new therapeutic frontiers for rhinovirus-induced asthma. This article reviews the recent advances of the literature on the regulated expression of type III Interferons and their receptor in association with Rhinovirus infection in asthmatic subjects.